Diblock Polymer Brush (PHEAA- b-PFMA) Microphase Separation Behavior and Anti-Protein Adsorption Performance - Wu, Hai-Xia (Langmuir : the ACS journal of surfaces and colloids, 2018)
In this paper, a series of amphiphilic diblock polymers of poly(hydroxyethylacrylamide)- b-poly(1H,1H-pentafluoropropyl methacrylate) (PHEAA- b-PFMA) were grafted from silicon wafer via surface-initiated atom transfer radical polymerization (SI-ATRP). Surface wettability and chemical compositions of the modified surfaces were characterized by contact angle goniometer and X-ray photoelectron spectroscopy (XPS) respectively. Molecular weight and polydispersity of each block were measured using gel permeation chromatography (GPC). The topography and the microphase separation behavior of PHEAA- b-PFMA surfaces were investigated by atomic force microscope (AFM). The results show that only when the grafting density (σ) and thickness of PHEAA brush were in the range of 0.9-1.3 (chain/nm2) and 6.6-15.1 nm, respectively, and the ratio of PFMA/PHEAA varied from 89/42 to 89/94, could the diblock copolymer phase separate into nanostructures. Further, the antiprotein adsorption performance of the modified surfaces against BSA, fibrinogen, and lysozyme was studied. The results indicated the modified surfaces could reduce the protein adsorption compared to the pristine silicon wafer. For Fibrinogen, the antiadsorption effect of PHEAA- b-PFMA-modified surfaces with microphase segregation was better than that of corresponding PHEAA modified surfaces. The results provide further evidence that surface composition and microphase segregation of fluorinated moieties of block copolymer brushes significantly impact protein adsorption behaviors